Minimizing carbon dioxide emission with distance for Tunisian public transportation via the dhouib-matrix-4-PMO method - Dhouib, Souhail; Elmabrouk, Jihene Jlassi; Dhouib, Saima (Edelweiss Applied Science and Technology, 2025)
One of the main causes of CO2 emissions is believed to be urban transit. It is now crucial to create a sustainable transportation system to reduce its negative effects on the environment. Therefore, the primary objective of this research is to propose a strategy for reducing both distance and carbon dioxide emissions in the context of public bus distribution in Tunisia. In this paper, we propose a Multi-Objective Traveling Salesman Problem (MOTSP) model that considers environmental factors, along with a novel metaheuristic called Dhouib-Matrix-4-PMO. In fact, DM4-PMO is based on the initial enhancement of the new Dhouib-Matrix-4 (DM4) method and is adapted to generate Pareto non-dominated set solutions. The algorithm has been evaluated, and the results demonstrate the effectiveness of the proposed methodology.